Design and Implementation of SCADA System for Sugar Production Line - Abdulsattar, Noor N. N.; Mustafa, Faiz F.; Hadi, Suha M. (Al-Khwarizmi Engineering Journal, 2019)
SCADA is the technology that allows the operator to gather data from one or more various facilities and to send control instructions to those facilities.  This paper represents an adaptable and low cost SCADA system for a particular sugar manufacturing process, by using Programmable Logic Controls (Siemens s7-1200, 1214Dc/ Dc/ Rly). The system will control and monitor the laboratory production line chose from sugar industry. The project comprises of two sections the first one is the hardware section that has been designed, and built using components suitable for making it for laboratory purposes, and the second section was the software as the PLC programming, designing the HMI, creating alarms and trending system. The system will have two HMI screens according to the two operating states of system (Automatic and Manual), the operator can choose between them by a selector switch, this method helps the operators when fixing a failure and wanting to check it without operating all the process. The result has accomplished the goals of controlling, the parameters (temperature, flow, humidity) were monitored, failure was detected by an alarm.